Reliance on Predicative Units as a Method of Analysing and Translating Amharic Written Texts - Fridman, Iosif (Aethiopica, 2019)
In analysing and translating Amharic texts, most foreign students have experienced major problems while trying to ‘redirect’ the rigidly leftbranching syntax of Amharic into the predominantly right-branching syntax of most European languages. The way out of this difficulty proposed by some teachers of Amharic consists in the so-called ‘translating from the end’ principle: the student begins to decipher the structure of an Amharic sentence from the finite verb form at its very end and gradually proceeds towards the beginning of the sentence, untangling—one by one—the syntactic structures involved. In the course of teaching Amharic, I have found this method largely inadequate for the purpose it is supposed to achieve. As an alternative to the ‘translating from the end’ method the author proposes another strategy which could be termed ‘reliance on predicative units’. In using this strategy, the student should, first of all, single out verb forms which are likely to perform the function of (final or dependent) predicates. The second step consists in delimiting groups, or units, headed by every such verb form. The third step is to provide a rough, working translation of every such unit without taking into consideration its relations to the other units in the sentence. The fourth, and final, step consists in joining the translations of the predicative units together; at this stage, detailed knowledge of Amharic morphosyntactic rules is very much required.